2013
DOI: 10.1080/10962247.2013.831384
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pen bedding and feeding high crude protein diets on manure composition and greenhouse gas emissions from a feedlot pen surface

Abstract: Greenhouse gas (GHG) emissions from concentrated animal feeding operations vary by stage of production and management practices. The objective of this research was to study the effect of two dietary crude protein levels (12 and 16%) fed to beef steers in pens with or without corn stover bedding. Manure characteristics and GHG emissions were measured from feedlot pen surfaces. Sixteen equal-sized feedlot pens (19 Â 23 m) were used. Eight were bedded approximately twice a week with corn stover and the remaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 36 publications
(42 reference statements)
1
1
0
Order By: Relevance
“…Total carbon (TC) in manure was significantly lower in August as compared to other months. In 2012 summer, Borhan et al [ 45 ] had also measured the nutrient composition of the manure in the same feed lot under similar condition and the values of nutrient parameter were almost comparable with this study.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Total carbon (TC) in manure was significantly lower in August as compared to other months. In 2012 summer, Borhan et al [ 45 ] had also measured the nutrient composition of the manure in the same feed lot under similar condition and the values of nutrient parameter were almost comparable with this study.…”
Section: Resultssupporting
confidence: 85%
“…In comparing the results with the previous study; in 2011, Rahman et al [ 40 ] simply measured GHG emission from the same feedlot pen surface and they found that CH 4 , CO 2 and N 2 O emission were 38, 26, and 17 g hd -1 d -1 , respectively, during the 2011 summer period. Similarly, in 2012, Borhan et al [ 45 ] studied the effects of two dietary crude protein levels (12 and 16 %) in the GHG emission on the similar conditions. They found that CH 4 , CO 2 and N 2 O emission ranged from 40–61, 31–43, and 50–116 gAU -1 d -1 (0.8–1.1, 593–431, and 1–1.9 g m -2 d -1 ), respectively, during the summer months.…”
Section: Resultsmentioning
confidence: 99%